Sobre la interiorización del espacio social - Méndez Rubio, Antonio (CIC. Cuadernos de Información y Comunicación, 2009)
The author explores the relationships between the exterior world and the inner world in the diverse types of messages and reproducing products of the mass media, analyzing the cultural roots, the ideological, political, and social features that these relationships show. The different reproducing cultural forms create passages and virtual spaces which mediates the space to link it with the inner life. Above all, the author finds that the meditating and informative processing of the public space has a direct link with the modern capitalism in its expansive and privatizing tendency, and it is essential to study today into depth the processes which connect the expansion pf cultural and informative spaces with the insight of the public space.
Keywords: Mediatising of the public space; Private space; Communication media; Globalization; Capitalism; Culture